SOFT POWER: BRICS CULTURAL DIPLOMACY AND THE REBALANCING OF GLOBAL NARRATIVES - Lee, Brice Tseen Fu; Kornphetcharat, Kotchaphop; Sims, Juan Pablo (UI Scholars Hub, 2025)
BRICS has broadened its agenda beyond finance to cultivate soft power through coordinated cultural diplomacy. Examining official statements, press releases, and scholarly commentary on the bloc’s flagship film, sports, and ministerial initiatives, this article shows that cooperation is advancing from one-off spectacles toward structured, recurring institutions. Findings indicate two simultaneous dynamics: outwardly, BRICS venues amplify Global-South perspectives that diversify international cultural flows; inwardly, member states use the same platforms to signal national prestige, revealing persistent status competition. The result is an early but uneven cultural architecture—one that counters Euro-Atlantic narrative dominance yet has not crystallized into a fully coherent BRICS identity. The study argues that success will hinge on tighter media coordination and concrete, mutually beneficial projects capable of deepening collective resonance while balancing internal hierarchies.